Graft Copolymers with Conducting Polymer Backbones: A Versatile Route to Functional Materials. Issue 1 (20th January 2016) - Strover, Lisa T.; Malmström, Jenny; Travas‐Sejdic, Jadranka
Abstract: Graft copolymers with a conducting polymer backbone are a promising class of materials for diverse applications including, but not limited to, organic electronics, stimuli‐responsive surfaces, sensors, and biomedical devices. These materials take advantage of the unique electrochemical and optoelectronic properties of conducting polymers, complemented by chemical and/or physical properties of the grafted sidechains. In this Personal Account, we discuss our work in designing functional surfaces based on graft copolymers with a conducting polymer backbone, in the context of broader developments in the field. We review the synthetic approaches available for the rational design of conducting‐polymer‐based graft copolymers, and examine the types of functional surfaces and soluble materials that may be engineered using these techniques. Abstract : Graft copolymers with a conducting polymer backbone are a promising class of materials for diverse applications such as organic electronics, stimuli‐responsive surfaces, sensors, and biomedical devices. In this Personal Account, we discuss our work in designing functional surfaces based on these, in the context of broader developments in the field.